2016
DOI: 10.1039/c5nj02333e
|View full text |Cite
|
Sign up to set email alerts
|

Wettability properties vary with different morphologies of ZnO nanoparticles deposited on glass and modified by stearic acid

Abstract: In the present study, variations in morphology and surface wettability are accomplished using different zinc sources for the deposition of zinc oxide (ZnO) nanoparticles on a glass surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Tuning surface wettability can be achieved by modifying surface energy or morphology [12]. For instance, in optoelectronic applications, the self-cleaning properties of semiconductor metal oxide thin films with different morphologies have been a subject of focus [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tuning surface wettability can be achieved by modifying surface energy or morphology [12]. For instance, in optoelectronic applications, the self-cleaning properties of semiconductor metal oxide thin films with different morphologies have been a subject of focus [10].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is largely used as an additive in rubbers, plastics, ceramics, glasses and pigments, and is one of the most relevant semiconducting material due to its optical and electrical properties [21]. Many studies are reported in the literature concerning the use of ZnO in the preparation of superhydrophobic rigid surfaces, some of which involved the chemical treatment with stearic acid (Figures S1 and S2) [22,23,24,25,26,27]. Lee et al reported on a facile approach for the fabrication of a superhydrophobicnanocoatings on different substrates (both rigid as silicon and flexible as polyethylene terephthalate (PET)) through a simple but long-lasting procedure based on the spin-coating deposition of a series of layers of ZnONPs, each subjected to a chemical modification step with stearic acid [20].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this objective, a rough surface structure is constructed and treated with a low surface energy material. In this process, the construction of an appropriately rough surface structure is crucial [5][6][7][8] . A rough copper surface can be obtained by several methods such as chemical oxidation 9,10) , chemical etching 11,12) , physical etching 13) , physical and chemical lm deposition 14) , and hydrothermal synthesis 15) .…”
Section: Introductionmentioning
confidence: 99%